ANALYSIS OF THE GROSS ADDED VALUE OF AGRICULTURAL PRODUCTION IN THE REPUBLIC OF SERBIA - Novaković, Tihomir; Tomaš Simin, Mirela; Novaković, Dragana; Mutavdžić, Beba (Economics of Agriculture, 2024)
This research analyzes the structure and economic impact of agricultural production in Serbia, focusing on gross value added (GVA). The aim is to identify the branches of agriculture that contribute the most to overall production value and quantify their impact on GVA. Basic descriptive statistics and multiple linear regression analysis were used to determine the individual contributions of agricultural sectors. The study covers data from the Statistical Office of the Republic of Serbia for the period 2007–2022. Results show that agriculture significantly influences the national economy, especially through crop and livestock production, with crop production, particularly cereals, having the largest impact on GVA. The conclusions suggest that shifting to more intensive agricultural methods and optimizing livestock production could improve economic outcomes. Policy recommendations include strategic investments in specific sectors to enhance efficiency and economic contributions. Integrated agricultural practices are also suggested to further strengthen the sector’s overall performance.